Restitution of the National Monetary System and the Introduction of Temporary Money: Prehistory and Realization - Jasienė, Meilė (Ekonomika, 2006)
The idea of the restitution of the Lithuanian national monetary system for the first time was discussed openly on May 26, 1988 at the meeting of scientists at the Institute of Economics of the Academy of Sciences, where professor Stasys Uosis for the first time openly expressed the idea of the restitution of the Lithuanian national monetary system.Some scientists, among them the nomenclature of soviet banks, spoke against the idea of litas.In spring 1989, the group of the creation of independent Lithuanian monetary and credit system was organized, in which lecturers of Vilnius University Finance and Credit Department and bankers-practitioners took part. In half a year the conception of independent Lithuanian monetary and credit system and the projects of related laws were prepared.When on March 11, 1990 the Independence was restored, the possibilities to create the real, functioning central bank and national currency appeared. But the newly re-established the Bank of Lithuania had neither premises nor resources. It had only several workers, the Board hadn’t been organized. When Vilius Baldisis was appointed Chairman of the Board of the Bank of Lithuania and the Statute of the Bank of Lithuania was approved, the main tasks in the monetary sphere were formulated, the concrete work began.On November 5, 1991 the Supreme Council adopted the publishing of Money Law. The Committee of Litas was founded. Its task was to fix the litas emission date. At the beginning of 1992 it was already prepared to introduce litas, but because of the inflation politics of the Government of that time the infroduct of litas became impossible - litas would quickly devaluate, the mere idea of litas as the national currency symbol would be discredited.The prices jumped up sharply, the lack of goods grew. The Government changed the order of selling the deficit goods by coupons (product cards). On July 29, 1991 the new common coupons were introduced. They were not money, but only universal trade cards. This change of the trade order did not diminish the problems. In this situation, the Bank of Lithuania suggested not to put coupons in circulation and only in case of necessity to use them as temporary money, but the government did not pay attention to this suggestion.The shortage of rouble cash began, the salaries, pensions, various payments and grants were not paid in lime. Rouble signs were printed and emitted in Russia. For the political and economical reasons there was no possibility to expect the accession of cash from the USSR State Bank, so the Bank of Lithuania was looking for possibilities to emit the substitutes of rouble. On May 1, 1992 new coupons as the substitutes of rouble were put in circulation. With their help the bigger part of the arrears was liquidated. AI the same lime trade by common coupons (universal trade cards) was stopped.Life changed the plans of the creation of national monetary system. It was decided to introduce temporary money. When the Government changed, the Committee of Litas on September 16, 1992 adopted the decision that from October 1, 1992 only temporary moneycoupons would be circulating in the territory of the Republic of Lithuania. Roubles were changed into coupons in the ratio 1:1. This way on October 1, 1992 the national currency was introduced and the own monetary system re-established in Lithuania.The Bank of Lithuania acquired the possibility 10 fulfil the main function of the Central Bank - to regulate the turnover of money, to apply instruments of monetary policy. The growth of the amount of money and inflation process slowed down, and from December I, 1992 the exchange rale of coupon against rouble became stronger. The variation of the exchange rate of coupon towards convertable currencies became smaller, though their exchange rates towards our money grew.The state had a possibility 10 prepare for changing temporary moneycoupons into litas.